Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1096/fj.07-8800com
|View full text |Cite
|
Sign up to set email alerts
|

Specific cleavage of agrin by neurotrypsin, a synaptic protease linked to mental retardation

Abstract: The synaptic serine protease neurotrypsin is thought to be important for adaptive synaptic processes required for cognitive functions, because humans deficient in neurotrypsin suffer from severe mental retardation. In the present study, we describe the biochemical characterization of neurotrypsin and its so far unique substrate agrin. In cell culture experiment as well as in neurotrypsin-deficient mice, we showed that agrin cleavage depends on neurotrypsin and occurs at two conserved sites. Neurotrypsin and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 34 publications
1
111
0
Order By: Relevance
“…Teq/neurotrypsin is of particular interest as a presenilin target given its likely role in memory and cognition. Specifically, Teq mutants in Drosophila have defects in memory formation, and neurotrypsin itself has been implicated in processing of agrin, which is an important synaptic component (14,15) Finally, neurotrypsin mutations in humans cause mental retardation (16). Mechanistically, we found that in MEFs the presence of a mature ␥-secretase complex, but not the autocatalytic endoproteolysis of PSEN1 or the processing of well known ␥-secretase substrates, is required to repress neurotrypsin and agrin cleavage.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Teq/neurotrypsin is of particular interest as a presenilin target given its likely role in memory and cognition. Specifically, Teq mutants in Drosophila have defects in memory formation, and neurotrypsin itself has been implicated in processing of agrin, which is an important synaptic component (14,15) Finally, neurotrypsin mutations in humans cause mental retardation (16). Mechanistically, we found that in MEFs the presence of a mature ␥-secretase complex, but not the autocatalytic endoproteolysis of PSEN1 or the processing of well known ␥-secretase substrates, is required to repress neurotrypsin and agrin cleavage.…”
mentioning
confidence: 76%
“…Reagents and Antibodies-Antibodies generated against agrin (R132), neurotrypsin (G95), and amyloid precursor protein-like (APPL) as well as purified Wnt3a were described previously (15,17,18). The anti-␣-tubulin (DM1A), anti-APP (22C11) to detect full-length APP, anti-PSEN1 (MAB5232), anti-GSK3␤ (07-1413), anti-actin (MAB1501), anti-H3K27me3 (07-449), anti-H3K4me3 (07-473), and anti-H3K9ac (07-352) antibodies were purchased from Millipore.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations